Gambaran Pengetahuan Ibu Tentang Gizi Seimbang dalam Pencegahan Stunting pada Balita Di Desa Tanjung Harapan Wilayah Kerja UPT Puskesmas Lipat Kain Tahun 2023 - Alia, Alia Lestari; Harahap, Dewi Anggriani; Dhilon, Dhini Anggraini (Evidence Midwifery Journal, 2024)
National nutritional problems among children under five can be seen from data from Riau Province in 2021, the prevalence of stunting was 27.4% in 2019, 22.3% in 2021 and decreased to 17% in 2022, while in Kampar district it was 25.7% in 2021, one of which is in the region The work of the UPT Puskesmas folding cloth includes 98 toddlers. As such, moms need to be aware of and comprehend the dietary requirements of their toddlers. The purpose of this study is to examine how women in Tanjung Harapan village, the UPT Puskesmas Fold Kain's operational region in 2023, describe their understanding of the importance of a balanced diet in preventing toddler stunting. This study employed a quantitative descriptive research design. 49 respondents made up the entire sample for this study, which was selected using the total sampling technique. A questionnaire with univariate analysis displayed in a frequency distribution is used as the data gathering instrument. According to the research's findings, mothers' understanding of the benefits of toddlers' nutritional needs is in the good category for 49 (100%) respondents, and mothers' understanding of the concept of balanced nutrition is in the good category for 41 (83.67%) respondents. 32 (65.31%) of the respondents who are under five fall into the good category. Similarly, 47 (95.92%) of the respondents describe their mothers' knowledge of food processing; 48 (97.95%) describe mothers' knowledge of factors that influence toddlers' nutritional status; and 30 (61.22%) describe mothers' knowledge of balanced nutrition. It is hoped that mothers in the UPT Puskesmas Folding Cloth work area can apply knowledge about balanced nutrition in order to prevent stunting so that the number of stunting incidents is reduced.